Peran Lembaga Zakat dalam Pemberdayaan Ekonomi Penerima Zakat: Studi Kasus BAZNAS Kota Jogja dan BAZNAS DIY - Sutrisno, Sutrisno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the role of zakat institutions in economic empowerment of zakat recipients, with a case study at BAZNAS Jogja City & BAZNAS DIY. This research uses descriptive qualitative methods. Data obtained through observation, interviews and documentation. There were seven informants in this research consisting of the Program Manager, Implementing Staff for zakat distribution, Program Facilitators and zakat recipients at each Zakat Institution studied. The research results concluded that BAZNAS Jogja City & BAZNAS DIY have played an optimal role in efforts to improve the economy of zakat recipients. The two zakat institutions have implemented several productive zakat programs aimed at empowering zakat recipients in the businesses they run. The strategy used is providing provisions to potential aid recipients, business training and providing business capital to zakat recipients. There are several obstacles faced by BAZNAS Jogja City & BAZNAS DIY in empowering the economy of zakat recipients, including zakat recipients not being optimal in running their businesses, especially in increasing sales. Thus, BAZNAS City and BAZNAS DIY need to provide assistance according to the problems experienced by zakat recipients to help and improve the businesses of zakat recipients. Keywords: Role of BAZNAS, Economic Empowerment, Zakat recipients.